FORWARD MODELING OF TIME-LAPSE MICROGRAVITY BY CONSIDERING WATER TABLE FLOW, SOIL COMPACTION AND SUBSIDENCE CAUSE BY GROUND WATER EXTRACTION, CASE STUDY BANDUNG BASIN AREA - Abdurrahman, Dadi
Author proposes a new approach for numerical calculation of time-lapse microgravity by considering parameters of groundwater flow, soil compaction, and subsidence caused by groundwater extraction. The time-lapse microgravity value is influenced by geometric and density changes factors. A decrease in groundwater level will changes rock density and perturb effective stress. Effective stress’s changes compaction, then changing the geometry and rock density. Compaction in the subsurface will affect the surface, and, if the compaction is big enough, might cause subsidence on the surface (changes in geometry). In this study, we model the physical phenomenon by connecting 7 parameters: pumping discharge, aquifer thickness, rock density, fluid density, porosity, specific storage, and hydraulic conductivity. The method was then applied to study the hydrological condition beneath Greater Bandung area, a mega city with population of more than 7 million lied on a sedimentary basin. Our results suggest that the aquifer system in some areas is consisted of loose sand which is still undergoing consolidation, yet experienced excessive ground water intake. We propose the same procedure to be applied to other big cities lied on a sedimentary basin as a key input for the ground water management in the town.